Examining the Effect of TED Talks on Improving English Speaking Skills: Students' Perceptions - Albion, Kevin Dario; Susiati, S (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2024)
Purpose: The purpose of this study is to describe Madiun secondary school students’ perceptions and analyze the effect of watching TED Talks on the development of their English-speaking skills. Methodology: The research employs a mixed-method approach involving class observations, surveys, and interviews with 135 tenthgrade students from a secondary school in Madiun. The data from surveys and interviews were analyzed using Miles & Huberman’s data analysis method, which includes data reduction, data display, and drawing conclusions. The teaching activities consisted of three phases—preliminary activities, main activities, and closing—that work together to create an effective and engaging teaching strategy. Results: The results show that 79% of the students responded positively to the use of TED Talks to improve their speaking skills, in line with Robin’s (2003) positive and negative perception theory. Overall, the study provides a comprehensive understanding of how TED Talks contribute to students’ speaking skill development, affirming that TED Talks have a positive effect and are perceived as an effective medium in the language learning process. Applications/Originality/Value: The application of this research is that TED Talks can be integrated into English language teaching as an engaging and effective tool to enhance students’ affective and cognitive experiences, thus supporting the improvement of speaking skills in secondary schools